An Analysis of Moral Value Potrayed in Paulo Coelho’s The Spy and Eka Kurniawan’s Cantik itu Luka: A Comparative Literature Analysis - Tambunan, Citra Mei Riana; Pardede, Martha (LingPoet: Journal of Linguistics and Literary Research, 2022)
This study discusses a comparative literary study of two literary works with different nations and languages, but with similar motif, which is Moral Values. This study uses the concept of Moral Values which provides the concept of values that have a Commitment to something greater than oneself, Self-respect but with humility, self-discipline, and acceptance of personal responsibility, Respect and caring for others, Caring for other living things and the environment. This study employed a qualitative descriptive method, that uses the data sources the two novels The Spy by Paulo Coelho and Cantik itu Luka by Eka Kurniawan and the data is obtained from novel quotes of the data in the form of words and sentences. Then, the results The novel The Spy fulfills these four moral values. Meanwhile, the novel Cantik itu Luka only fulfills three of the four moral values.